Refining Used Cooking Oil Using Tapioca Starch (Manihot esculenta) and Lime (Citrus aurantifolia) - Hadiah, Fitri; Alisya, Rona; Fitriyani, Della (Universitas Trunojoyo Madura, 2024)
Used cooking oil is cooking oil that has been used multiple times, leading to decreased in quality. This decline in quality occurs due to the degradation of the cooking oil's components. The community, especially traders, prefers to use used cooking oil or reuse cooking oil multiple times because it is more profitable than using fresh cooking oil. Using this used cooking oil can cause cholesterol issues in the body. This research aims to refine used cooking oil using carbon-rich tapioca starch and antioxidant-rich lime which is expected to restore the quality of used cooking oil. This research uses the experimental method by varying the mass of the adsorbent, specifically the ratio of tapioca starch mass at 5%, 10%, and 15%, and the lime mass ratio at 5%, 10%, 15%, and 20%. The used cooking oil refining process was conducted by mixing used cooking oil and adsorbents for one hour at a speed of 200 rpm and then allowed to stand for 2 days. This research aims to study the effect of the amount of tapioca starch and lime as adsorbents on the viscosity, density, and acid number of refined used cooking oil. The optimal use of adsorbent is 20% tapioca starch and 10% lime, resulting in a density of 0.9760 g/cm³, viscosity of 18.9452, and an acid number of 2.8719 mg KOH/gram oil.